Second chance at Sunflower ranch - Brown, Carolyn, 1948- (Forever, 2021)
Returning home to Sunflower ranch to take care of his aging foster parents, retired combat medic Jesse Ryan isn't prepared for his parents' live-in nurse, the woman he always regretted leaving behind, who reveals a shocking secret.